Investigation of biological characteristics of fruit development and physiological disorders of Musang King durian (Durio zibethinus Murr.) - Duong Nguyen Huynh; Ngan Huynh Thi Thanh; Linh Bui Khanh; Thang La Cao; Thuc Le Vinh; Van Hau Tran (Open Agriculture)
This study investigates the biological characteristics of fruit development and physiological disorders in the Musang King durian (Durio zibethinus Murr.). The experiment was conducted on 20 7-year-old trees cultivated in Nhon Nghia commune, Phong Dien district, Can Tho City, from October 2023 to July 2024. The results revealed a 7-day flowering period post-first bloom, with peak blooming observed between the second and fourth days. Flower opening commenced at 16:00–17:00 h, achieving a fruit set rate of 93%. Fruit development spanned 90 days after fruit set (DAFS) and was characterized by three distinct growth phases: slow growth (0–28 DAFS), rapid growth (28–70 DAFS), and ripening (70–90 DAFS). Immature fruit drop primarily occurred within the first 14 days (35.0%). The fruit’s flesh began to form at 42 DAFS, reaching its maximum growth rate by 56 DAFS. At harvest, fruits averaged 2161.8 ± 74.7 g, with an edible portion constituting 24.8% of total weight. Physiological disorders, including hardened flesh and discoloration, were first observed at 70 DAFS (16.7%), increasing to 30.0, 6.7, and 13.3% at harvest for hardened flesh, aril tip burn, and flesh discoloration, respectively. These disorders significantly impacted commercial fruit quality.